The euro treasury plan - Jörg Bibow (Levy Economics Institute of Bard College, 2014)
Contrary to German chancellor Angela Merkel's recent claim, the euro crisis is not nearly over but remains unresolved, leaving the eurozone extraordinarily vulnerable to renewed stresses. In fact, as the reforms agreed to so far have failed to turn the flawed and dysfunctional euro regime into a viable one, the current calm in financial markets is deceiving, and unlikely to last. The euro regime's essential flaw and ultimate source of vulnerability is the decoupling of central bank and treasury institutions in the euro currency union. In this public policy brief, Research Associate Jörg Bibow proposes a Euro Treasury scheme to properly fix the regime and resolve the euro crisis. The Euro Treasury would establish the treasury-central bank axis of power that exists at the center of control in sovereign states. Since the eurozone is not actually a sovereign state, the proposed treasury is specifically designed not to be a transfer union; no mutualization of existing national public debts is involved either. The Euro Treasury would be the means to pool future eurozone public investment spending, funded by proper eurozone treasury securities, and benefits and contributions would be shared across the currency union based on members' GDP shares. The Euro Treasury would not only heal the euro's potentially fatal birth defects but also provide the needed stimulus to end the crisis in the eurozone.
Keywords: 330